Beach erosion under rising sea‐level modulated by coastal geomorphology and sediment availability on carbonate reef‐fringed island coasts. Issue 5 (15th June 2016) - Romine, Bradley M.; Fletcher, Charles H.; Frazer, L. Neil; Anderson, Tiffany R.
Abstract: This study addresses gaps in understanding the relative roles of sea‐level change, coastal geomorphology and sediment availability in driving beach erosion at the scale of individual beaches. Patterns of historical shoreline change are examined for spatial relationships to geomorphology and for temporal relationships to late‐Holocene and modern sea‐level change. The study area shoreline on the north‐east coast of Oahu, Hawaii, is characterized by a series of kilometre‐long beaches with repeated headland‐embayed morphology fronted by a carbonate fringing reef. The beaches are the seaward edge of a carbonate sand‐rich coastal strand plain, a common morphological setting in tectonically stable tropical island coasts. Multiple lines of geological evidence indicate that the strand plain prograded atop a fringing reef platform during a period of late‐Holocene sea‐level fall. Analysis of historical shoreline changes indicates an overall trend of erosion (shoreline recession) along headland sections of beach and an overall trend of stable to accreting beaches along adjoining embayed sections. Eighty‐eight per cent of headland beaches eroded over the past century at an average rate of −0·12 ± 0·03 m yr −1 . In contrast, 56% of embayed beaches accreted at an average rate of 0·04 ± 0·03 m yr −1 . Given over a century of global (and local) sea‐level rise, the data indicate that embayed beaches are showing remarkable resiliency. The pattern of headland beach erosion and stable to accreting embayments suggests a shift from accretion to erosion particular to the headland beaches with the initiation of modern sea‐level rise. These results emphasize the need to account for localized variations in beach erosion related to geomorphology and alongshore sediment transport in attempting to forecast future shoreline change under increasing sea‐level rise.